Insights into the Regulatory Properties of Human Adenylyl Cyclase Type 9 - Baldwin, Tanya A. (Mol Pharmacol, 2019)
Membrane-bound adenylyl cyclase (AC) isoforms have distinct regulatory mechanisms that contribute to their signaling specificity and physiologic roles. Although insight into the physiologic relevance of AC9 has progressed, the understanding of AC9 regulation is muddled with conflicting studies. Currently, modes of AC9 regulation include stimulation by Gαs, protein kinase C (PKC) βII, or calcium-calmodulin kinase II (CaMKII) and inhibition by Gαi/o, novel PKC isoforms, or calcium-calcineurin. Conversely, the original cloning of human AC9 reported that AC9 is insensitive to Gαi inhibition. The purpose of our study was to clarify which proposed regulators of AC9 act directly or indirectly, particularly with respect to Gαi/o. The proposed regulators, including G proteins (Gαs, Gαi, Gαo, Gβγ), protein kinases (PKCβII, CaMKII), and forskolin, were systematically evaluated using classic in vitro AC assays and cell-based cAMP accumulation assays in COS-7 cells. Our studies show that AC9 is directly regulated by Gαs with weak conditional activation by forskolin; other modes of proposed regulation either occur indirectly or possibly require additional scaffolding proteins to facilitate regulation. We also show that AC9 contributes to basal cAMP production; knockdown or knockout of endogenous AC9 reduces basal AC activity in COS-7 cells and splenocytes. Importantly, although AC9 is not directly inhibited by Gαi/o, it can heterodimerize with Gαi/o-regulated isoforms, AC5 and AC6.